2021
DOI: 10.31729/jnma.6397
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication in Primary Dysmenorrhea among Medical and Nursing Undergraduate Students of a Tertiary Care Hospital: A Descriptive Cross-sectional Study

Abstract: Introduction: Primary dysmenorrhea is one of the most common gynecological problems among adolescent females. It is defined as painful menses in women with normal pelvic anatomy, usually beginning during adolescence. This study aims to find out prevalence of self-medication practice in primary dysmenorrhea among medical and nursing undergraduate students. Methods: A descriptive cross-sectional study was conducted in a tertiary care hospital from November 2020 to March 2021 after taking ethical approval from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…Other research observed a similar or an even higher prevalence of self-medication (76-92%) [24,[27][28][29]. Moreover, the percentage of self-medication among nursing and medical students was analysed in specific pathologies such as dysmenorrhea (65%) [30] or musculoskeletal pain (59.9%) [31], as well as with specific drugs, such as antibiotics (52.7%) [9] or analgesics (very different prevalences between studies, ranging from 39% [32,33] to 87% [21]).…”
Section: Discussionmentioning
confidence: 94%
“…Other research observed a similar or an even higher prevalence of self-medication (76-92%) [24,[27][28][29]. Moreover, the percentage of self-medication among nursing and medical students was analysed in specific pathologies such as dysmenorrhea (65%) [30] or musculoskeletal pain (59.9%) [31], as well as with specific drugs, such as antibiotics (52.7%) [9] or analgesics (very different prevalences between studies, ranging from 39% [32,33] to 87% [21]).…”
Section: Discussionmentioning
confidence: 94%
“…The frequency of dysmenorrhea among young women ranges from 16 to 93%, with a perception of severe pain in 2 to 29%, depending on the study population (25), which has been associated with self-medication with analgesics and anti-inflammatories in 65% of cases (26). The possibility of therapeutic failure, adverse effects, and even abuse (high nontherapeutic doses) for rapid pain relief indicates the importance of gynecological assessment for young women who experience recurrent dysmenorrhea (27).…”
Section: Discussionmentioning
confidence: 99%
“…These symptoms were 70-80% improved with mefenamic acid use only. Moreover, various studies noted mefenamic acid to be the most commonly used and effective among various drugs used for self-medication 20,21 . Also, it was delineated that mefenamic acid had a comparable effect to clecoxib in relieving symptoms 22 .…”
Section: Yes Nomentioning
confidence: 99%